The Immune System during Covid-19 Pandemic: An Islamic and Scientific Perspective - Irani Suryakartini Inaldi; Anita Puji Astutik (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article aims to determine the relationship between science and the Islamic perspective on the immunity concept during the Covid-19 pandemic and to determine the relationship with the proposition contained in the Qur'an and hadith. This research is a literature study method using data sources from journals and library reviews. The results of this study indicate that maintaining the immunity during the Covid-19 pandemic is in accordance with Islamic advice that had been implemented for a long time before the pandemic. It shows that Islam and Science have a balanced interrelation that complements each other. From an Islamic perspective, increasing immunity must be supported through the scientific way by maintaining health, cleanliness, environment, food, exercise, and vaccination. Even commands that are worth worship, such as listening, reading, and implementing the Qur'an, ablution, prayer movements, and maintaining social relationships, have been proven to increase body immunity during the Covid-19 pandemic. This result demonstrates that the Islamic perspective it is more complex than scientific discovery; this is the wisdom of studying science to prove the truth of the Qur'an and hadith.